Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Language indicators over time: Interactive Dashboard - Statistics Canada (Statistics Canada, 2025)

Diversité linguistique au Canada, 2021 : tableau de bord interactif - Statistique Canada (2021)

How poverty rates differed by language in Quebec, New Brunswick and Ontario in 2021 - Statistique Canada (2026)

Indicateurs linguistiques au fil du temps : tableau de bord interactif - Statistique Canada (Statistique Canada, 2025)

Language diversity in Canada, 2021: Interactive dashboard. - Statistique Canada (2026)

Poverty rate of the bilingual population in Quebec, New Brunswick and Ontario in 2021 - Statistique Canada (2026)

Taux de pauvreté au sein de la population bilingue du Québec, du Nouveau-Brunswick et de l’Ontario, 2021 - Statistique Canada (2021)

Variations dans les taux de pauvreté selon la langue au Québec, au Nouveau-Brunswick et en Ontario - Statistique Canada (2021)

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.